POTRET PERILAKU MENYIMPANG DALAM NOVEL HUJAN DAN TEDUH KARYA WULAN DEWATRA - Khaswara, Dewa; Zulfahdli, Zulfadhli (Jurnal Bahasa dan Sastra, 2019)
This study was conducted aimed at analyzing deviant behavior in the Hujan dan Teduh novels by Wulan Dewatra. In addition, with the existence of this study, it can be seen the forms of deviant behavior, factors that cause deviant behavior, and the effects of deviant behavior in the novel. In this study, used a type of qualitative research with descriptive methods. The findings in this study are, (1) the forms of deviant behavior in Wulan Dewatra's Hujan dan Teduh novels include, antisocial, sexual relations outside marriage, homosexuality, and violence, (2) factors that cause deviant behavior in the novel Hujan dan Teduh Wulan Dewatra's work includes unhealthy mental attitude factors, impingement of disappointment, and deviant learning processes. (3) the impact of deviant behavior in the Hujan dan Teduh novels by Wulan Dewatra covers crime and the fading of values and norms.Keywords: Disorder behaviour, Hujan dan Teduh, Sociology Literature